Experimental Study on the Impact of Weather Conditions on Wide Code Division Multiple Access Signals in Nigeria - Eli-Chukwu, N. C.; Onoh, G. N. (Engineering, Technology & Applied Science Research, 2019)
In cellular network activities, before a site is integrated it is expected that each cell of the site meets the Nigerian Communication Commission (NCC) standard of ≥98% for both service accessibility and call completion rate which in turn depicts a ≤2% in both blocked call rate (BCR) and dropped call rate (DCR). It is suggested that weather conditions have a very strong negative effect on the performance of wideband code division multiple access (WCDMA) network as it could lead to signal attenuation or change the polarization. In this paper, we study the impact of weather conditions on WCDMA network in Nigeria. To achieve this, network samples (log-files) were collected weekly during a driving test in Enugu State Nigeria for a period of five years for both rainy and dry seasons, in which blocked and dropped calls were extracted. Results show that during adverse weather conditions, BCR and DCR rise greater than 8% and 4% respectively. Although with a slight relationship between the weather conditions, the weather condition during the dry season has a better-blocked call rate of 8.76% in comparison with the rainy season with 12.89%. Calls tend to drop more during the dry season. From the outcome of the experiment, a model was developed for predicting an unknown network call statistics variables.